Effects of Different Vegetable Rotations on Fungal Community Structure in Continuous Tomato Cropping Matrix in Greenhouse - Lyu, Jian; Jin, Li; Jin, Ning; Xie, Jianming; Xiao, Xuemei; Hu, Linli; Tang, Zhongqi; Wu, Yue; Niu, Lijuan; Yu, Jihua (Frontiers in Microbiology, 2020)
Abstract: Intensive greenhouse vegetable cultivation aggravates continuous cropping, resulting in disturbance of the microbial community structure and diversity in the soil matrix. In this study, we evaluated the diversity of the rhizosphere matrix fungi in rotation and continuous cropping systems by using high-throughput sequencing analysis of substrates under 6-year continuous tomato cropping and rotation with cabbage, bean, or celery in greenhouse pots. The results showed that fungal richness in the cabbage rotation treatment (B) was significantly lower than that of other treatments, and fungal diversities of treatment B and the bean rotation treatment (D) were significantly lower than that of continuous tomato cropping (CK). Contrastingly, the celery rotation treatment (Q) increased the fungal diversity and richness. Furthermore, principal coordinate analysis showed that the fungal soil community structure of each rotation treatment was different from that of CK. The relative abundances of several harmful fungi (such as Pseudogymnoascus, Gibberella, and Pyrenochaeta) in control CK were significantly higher than those in rotation treatments. In addition, the matrix electrical conductivity, organic matter, total K, and available P in treatments B and D were significantly higher than those in control CK. Moreover, pH and total N of treatment Q were significantly higher than those of control CK. Most fungi were positively correlated with organic matter and available P, and negatively correlated with pH. Therefore, rotation with celery can improve the abundance and diversity of fungi in continuous tomato cropping substrates, and reduce the relative abundance of harmful fungi. These results indicated that rotation of celery and tomato can effectively maintain the ecological balance of the substrate microenvironment and provide a more effective way to prevent the problems of continuous tomato cropping in greenhouse.